Influence of emulsifiers and fat type on the shear-induced destabilisation of partially crystalline oil-in-water emulsions and corresponding aeration properties : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Manawatū, New Zealand - Henderson, Stella Simone (Massey University, 2022)
UHT whipping cream is an oil-in-water emulsion characteristically containing between 35-40% milk fat. A whipped cream is made up of three immiscible phases: air, fat and water. Air bubbles are stabilized by a network of partially coalesced fat globules and proteins, induced by mechanical forces (whipping). The percentage of solid fat and crystal morphology in dairy creams play a critical role in determining functional properties as it influences the degree of partial coalescence. The solid fat content of New Zealand milk fat can change depending on the stage of lactation, resulting in inconsistent functionality of creams. The purpose of this research was to investigate the influence of the oil-water interfacial film composition, emulsifiers and fat crystallization on the stability, structure and functionality of model partially crystalline oil-in-water emulsions for whipping cream applications. A bench scale model whipping cream system was developed with the ability to destabilise under shear. The model system was used to investigate the influence of emulsifiers and the seasonal variation in SFC on whipping cream functionality. This research was spilt into two main sections. Firstly, the the impact of LACTEM, MDG and Tween 80 on the destabilization and crystallization of milk fat in the model system was studied. Secondly, the impact of seasonal variation of solid fat content and non-dairy fat/oil blends on whipping cream functionality was studied. Formulations were analyzed through emulsion characteristics (PSD, FGSD, composition, protein surface load), crystallization behaviour, microstructure and whipping properties (whipping time, overrun, foam firmness). A key method used throughout this research to determine mechanisms was the ‘stop and return’ DSC method. This method was able to identify small changes to the formulation which impacted polymorphic transition and functionality. The relative solid fat content was used to identify significant correlations between blends of fats/oil and functionality. Results suggest that LACTEM significantly increased overrun but resulted in poor chilled foam stability probably due to the mixed layer of partially coalesced fat and proteins stabilizing air bubbles. MDG resulted in an emulsion that was stable against shear-induced aggregation, leading to long whipping times and weak foam structure. Tween80 resulted in fast destabilization of fat globules but could not efficiently incorporate air bubbles, leading to dense foams with minimal overrun. It was found that generally, a higher initial formation of α-crystals resulted in a more effective fat globule destabilization during whipping. It is recommended that the impact of emulsifier blends on the model system is investigated. Emulsifiers are rarely used singularly in whipping creams, and often require careful formulation to produce desired functionality through balancing the inhibition and promotion of destabilization. Results suggest the SFC of an emulsion impacts functionality. A high SFC did not cause significant differences in functionality and may improve foam structure. A low SFC resulted in longer whipping times, lower overrun and softer foams with a less defined foam structure. It is recommended that extra caution is taken when formulating with early season cream due to the low SFC. Potential solutions could include the addition of hard fraction AMF or adjusting emulsifier levels to account for the reduced SFC. Hard fraction palm oil and canola oil were used in emulsions to determine if SFC is a key driving force in influencing functionality. Both provided some potential benefits to the functionality and manufacturing costs as both palm oil and canola oil are typically cheaper than AMF. Hard palm fraction may provide improved whipping properties at a lower SFC compared to pure AMF due to the amount of unsaturated fatty acids. Canola oil can potentially be a replacement for a percentage of milk fat in whipping creams if the SFC is adequate. It is recommended that the feasibility of including hard palm fraction and canola oil in whipping cream formulations is investigated as both provided some potential benefits to the functionality and manufacturing costs.
Keywords: 300607 Food technology